Epilepsy in children - Holmes, Gregory L. (Henry Stewart Talks, 2011)
Incidence of Seizures, Classification of Seizures, Prevalence of Generalized and Partial Seizures, Epileptic Syndromes, Benign Familial Neonatal Seizures, Generalized Epilepsy Febrile Seizures +, Idiopathic Focal Epilepsies of Infancy and Childhood, Benign Rolandic Epilepsy, Idiopathic Generalized Seizures, Epileptic Encephalopathies, Infantile Spasms, Lennox-Gastaut Syndrome, Epilepsy in Association with Other Neurological Conditions, Angelman Syndrome, Tuberous Sclerosis, Rett Syndrome, Fragile X Syndrome, Lissencephaly
Archived at 2021/05/30